Choroid plexus cysts on 7T MRI: Relationship to aging and neurodegenerative diseases - Zhen, Zhiming; Zhang, Ruiting; Gui, Li; Chen, Jiafei; Xu, Siyao; Deng, Lihua; Yu, Yaling; Liu, He; Chen, Kang; Han, Qi; Hsu, Yi‐Cheng; Cheng, Yue; et al. (Alzheimer's & dementia, 2025)
INTRODUCTION The choroid plexus (CP) may play a crucial role in brain degeneration. We aim to assess whether CP cysts (CPCs), defined using ultra‐high field magnetic resonance imaging (MRI), relate to aging and neurodegeneration. METHODS We used multi‐sequence 7T MRI to observe CPCs, characterizing their presence and characteristics in healthy younger controls, healthy older controls (OCs), patients with Alzheimer's disease (AD), patients with Parkinson's disease (PD), and patients with uremic encephalopathy. CP volume (CPV) and CPC characteristics were compared across groups, and associations between CPV and CPC features were analyzed across all subjects. RESULTS The AD group showed a significantly higher presence and number of CPCs compared to other groups and also had a significantly larger CPV than healthy OCs. The number and size of CPCs were associated with CPV. DISCUSSION 7T MRI offers a distinct advantage in observing CPCs, and the high prevalence of CPCs in patients with AD warrants further investigation. Highlights 7T MRI enables visualization of the fine structures of the choroid plexus. Patients with Alzheimer's disease (AD) exhibit a higher number of choroid plexus cysts (CPCs) compared to healthy older adults and other patient groups. CPCs may serve as an auxiliary marker for AD.